An unusual neuroimaging finding and response to immunotherapy in a child with genetically confirmed vanishing white matter disease. (March 2017) - Singh, Rahul Raman; Livingston, John; Lim, Ming; Berry, Ian R.; Siddiqui, Ata
Abstract: Background: We present an unusual neuroimaging finding in a young girl with genetically confirmed vanishing white matter disease and a possible response to immunotherapy. Methods and results: 2.5 yr old girl, presented with acute onset unsteadiness and encephalopathy following a viral illness. MRI showed global symmetric white matter abnormality, with symmetric enhancement of cranial nerves (III and V) and of cervical and lumbar roots. She received immunotherapy for her encephalopathic illness with white matter changes. Follow up neuroimaging showed resolution of white matter edema and resolution of the change in the brainstem. Genetic testing confirmed a diagnosis of vanishing white matter disease (VWMD). Conclusion: Craniospinal nerve enhancement and possible response to immunotherapy has not been described in vanishing white matter disease.